Faculty Development: Measuring Unintended Consequences of Individual Participation in a Community of Practice - Kenda S. Grover; Shelly Walters; Kit Kacirek (Adult Education Research Conference, 2015)
The purpose of this study is to explore the impact of outcomes associated with self-directed learners’ participation in a Community of Practice (CoP) for faculty teaching in an online environment. The research examines how faculty members perceive their involvement impacts their teaching.
Keywords: community of practice; faculty development